2015
DOI: 10.1371/journal.pone.0121831
|View full text |Cite
|
Sign up to set email alerts
|

Dead Element Replicating: Degenerate R2 Element Replication and rDNA Genomic Turnover in the Bacillus rossius Stick Insect (Insecta: Phasmida)

Abstract: R2 is an extensively investigated non-LTR retrotransposon that specifically inserts into the 28S rRNA gene sequences of a wide range of metazoans, disrupting its functionality. During R2 integration, first strand synthesis can be incomplete so that 5’ end deleted copies are occasionally inserted. While active R2 copies repopulate the locus by retrotransposing, the non-functional truncated elements should frequently be eliminated by molecular drive processes leading to the concerted evolution of the rDNA array(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This apparent absence of homogenisation is indicative of extremely high mutation rates and/or considerable periods of time since the arrays last homogenised. Such variability contrasts with the situation in some animals where pseudogenes (transposon-inserted) seem to undergo at least partial homogenisation (Eickbush et al 1997 ; Glass et al 2008 ; Martoni et al 2015 ). The high homogeneity of 18S reads in D. lowei (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…This apparent absence of homogenisation is indicative of extremely high mutation rates and/or considerable periods of time since the arrays last homogenised. Such variability contrasts with the situation in some animals where pseudogenes (transposon-inserted) seem to undergo at least partial homogenisation (Eickbush et al 1997 ; Glass et al 2008 ; Martoni et al 2015 ). The high homogeneity of 18S reads in D. lowei (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…As far as R2 is concerned, we showed that the B. rossius genome hosts a functional (R2Br fun ) and a closely related, degenerate (R2Br deg ) element (Bonandin et al, 2014). Both elements actively replicate, but while R2Br fun showed a canonical pattern of a functional R2, R2Br deg copies are exclusively full length, that is, they have no associated 5 -end deletions, and lost the ability to fold into the ribozyme necessary for R2 RNA maturation, suggesting they replicate via 28S rDNA unequal recombination (Martoni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This element shows a complete ORF of 2739 bp encoding a protein of 912 amino acids. Interestingly, in a 5′ end sequence survey carried out in B. rossius 34 , an incomplete element was retrieved (R2Br del ), showing 99% of similarity with R2Bgm del and sharing the same internal deletion. The R2Br del fragment encompasses the whole 5′ UTR and the first 1293 bp of the ORF; the protein sequence obtained from that part of the ORF is 430 amino acids long, and the RT domain was only partially covered.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent comparisons involved presently isolated elements ( B. atticus : R2Ba; B. g. grandii : R2Bgg A and R2Bgg B ; B. g. benazzii : R2Bgb; B. g. maretimi : R2Bgm and R2Bgm del Fig. 1 ) together with previously identified ones ( B. rossius : R2Br fun , R2Br deg and R2Br del 32 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation